Historical climate change influenced the phylogeographical patterns of the brown alga Colpomenia sinuosa in the southern China - Xiaohan Song; Jie Zhang; Yuqun Du; Shuang Li; Yiping Shen; Yude Lin; Zimin Hu; Delin Duan (Algae, 2025)
Historical climate changes significantly influenced the phylogeographical patterns of intertidal macroalgae. The brown alga Colpomenia sinuosa was common in warmer waters worldwide, providing an ideal model for genetic diversity and distribution research. C. sinuosa has abundant biomass in the coastal South China Sea, which is a well-known hotspot on marine biodiversity. Here, we analyzed its population structure and demographic history using mitochondrial cox3, atp6, and chloroplast rbcL. We detected a genetic diversity pattern of high haplotype diversity and low nucleotide diversity at the intraspecific level, and our results revealed 2 main clades within C. sinuosa with obvious genetic differentiation among most populations. Furthermore, we detected 5 genetic lineages in concatenated dataset, and the regional isolation was regarded as dominating factor for genetic differentiation. The demographic history suggested that C. sinuosa was first diverged in late Oligocene, then underwent dynamic changes during the Pleistocene. Historical vicariance caused by Pleistocene glaciation events may account for present phylogeographic pattern. Moreover, ocean current and coastal topography of northern South China Sea might participate in shaping present genetic structure. Utilizing C. sinuosa as a model material, we suggested that Dongfang in southwestern Hainan and Sanya in southern Hainan should be regarded as independent management units and give priorities to seaweed resource conservation. In the future, we’ll enlarge our study range and sample collection, and further investigate the genetic distribution pattern of C. sinuosa at larger scale. Our study enriched insights into the historical glacial influences on seaweed phylogeographical patterns, and provided theoretical evidence for seaweed management of southern China.